THE FORMATION OF RIMS ON CALCIUM-ALUMINUM-RICH INCLUSIONS: STEP I-FLASH HEATING - Wark D.; Boynton W.V. (My University, 2001)
Wark-Lovering rims of six calcium-aluminum-rich inclusions (CAIs) representing the main CAI types and groups in Allende, Efremovka and Vigarano were microsurgically separated and analysed by neutron activation analysis (NAA). All the rims have similar ∼4x enrichments, relative to the interiors, of highly refractory lithophile and siderophile elements. The NAA results are confirmed by ion microprobe and scanning electron microscope (SEM) analyses of rim perovskites and rim metal grains. Less refractory Eu, Yb, V, Sr, Ca and Ni are less enriched in the rims. The refractory element patterns in the rims parallel the patterns in the outer parts of the CAIs. In particular, the rims on type B1 CAIs have the igneously fractionated rare earth element (REE) pattern of the melilite mantle below the rim and not the REE pattern of the bulk CAI, proving that the refractory elements in the rims were derived from the outer mantle and were not condensates onto the CAIs. The refractory elements were enriched in an Al2O3-rich residue <50 μm thick after the most volatile ∼80% of the outermost 200 μm of each CAI had been volatilized, including much Mg, Si and Ca. Some volatilization occurred below the rim, and created refractory partial melts that crystallized hibonite and gehlenitic melilite. The required “flash heating” probably exceeded 2000 °C, but for only a few seconds, in order to melt only the outer CAI and to unselectively volatilize slow-diffusing O isotopes which show no mass fractionation in the rim. The volatilization did, however, produce “heavy” mass-fractionated Mg in rims. In some CAIs this was later obscured when “normal” Mg diffused in from accreted olivine grains at relatively high temperature (not the lower temperature meteorite metamorphism) and created the ~50 μm set of monomineralic rim layers of pyroxene, melilite and spinel.